2018
DOI: 10.1038/s41409-017-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal obstruction syndrome/veno-occlusive disease after high-dose intravenous busulfan/melphalan conditioning therapy in high-risk Ewing Sarcoma

Abstract: This mono-institutional observational study was conducted to determine incidence, severity, risk factors, and outcome of sinusoidal obstruction syndrome/veno-occlusive disease (SOS/VOD) in high-risk Ewing sarcoma (ES) patients treated with intravenous busulfan and melphalan (BU-MEL) followed by autologous stem cell transplantation (ASCT). During the past 10 years, 75 consecutive ES patients resulted evaluable for the analysis. After diagnosis of SOS/VOD, defibrotide therapy was started as soon as the medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(78 reference statements)
0
4
0
1
Order By: Relevance
“…Pharmacokinetics of plasma busulfan were monitored in all patients. Risk factors for VOD/SOS identified in these studies following univariate, but not multivariate, analysis included cyclophosphamide in an adult study [37] and previous radiation therapy in adults (but not in children in the same study) with high-risk Ewing sarcoma [40]. Transplantation-related factors that reduced the risk of VOD/SOS were reported in 2 pediatric studies [30,39].…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetics of plasma busulfan were monitored in all patients. Risk factors for VOD/SOS identified in these studies following univariate, but not multivariate, analysis included cyclophosphamide in an adult study [37] and previous radiation therapy in adults (but not in children in the same study) with high-risk Ewing sarcoma [40]. Transplantation-related factors that reduced the risk of VOD/SOS were reported in 2 pediatric studies [30,39].…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 99%
“…The recently reported data demonstrate that although certain risk factors are established for VOD/SOS, independent risk factors may vary across populations and may include risks not previously noted in the literature. In addition, although review data indicate that VOD/SOS occurs most commonly after allogeneic HSCT [4], 3 recent studies (adult and pediatric) in autologous HSCT reported VOD/SOS incidence of approximately 7%, 8%, and 31% (Table 5) [5,36,40]. Other studies have also reported the incidence of VOD/SOS in patients receiving haploidentical HSCT [45,46], including delayed cases (e.g., median onset 44.5 days post-HSCT) [46].…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 99%
“…For patients with solid tumors, previous evidence suggests that various regimens, such as actinomycin D, high-dose cyclophosphamide, busulfan and melphalan followed by autologous stem cell rescue, and other highintensity chemotherapy regimens, with or without radiation therapy, may pose a risk to develop SOS, although the cumulative incidence is still rare. 2,[9][10][11][12][13][14] For patients with acute lymphoblastic leukemia/lymphoma, the incidence of SOS in the absence of HSCT is also unknown, but the most well-known risk factor for this patient population is the use of 6-TG. 3,4 6-TG is thought to be a more potent thiopurine than its analog 6-MP; however, increased toxicities associated with 6-TG have historically limited its utilization.…”
Section: Discussionmentioning
confidence: 99%
“…SOS may affect up to 27% of pediatric patients undergoing allogeneic HSCT:1 the incidence in oncology patients, in the absence of allogeneic HSCT, is more difficult to quantify. For patients with solid tumors, previous evidence suggests that various regimens, such as actinomycin D, high-dose cyclophosphamide, busulfan and melphalan followed by autologous stem cell rescue, and other high-intensity chemotherapy regimens, with or without radiation therapy, may pose a risk to develop SOS, although the cumulative incidence is still rare 2,9–14…”
Section: Discussionmentioning
confidence: 99%
“…Это может объясняться различиями в индукционной терапии, возрастом и более поздними сроками приживления в исследованной когорте. Полученные данные близки к частоте веноокклюзионной болезни печени в близкой по возрастным характеристикам когорте пациентов с опухолями семейства саркомы Юинга, получивших тот же режим кондиционирования [25]. Только 1 смерть непосредственно связана с токсичностью процедуры и еще в 1 случае смерть больного связана с последствиями геморрагического инсульта, произошедшего после восстановления показателей гемопоэза при значениях тромбоцитов более 20 × 10 9 .…”
Section: Discussionunclassified